PEMBINAAN ORANG DEWASA KRISTEN BERDASARKAN KONSEP PEMBELAJARAN PARTISIPATIF - Sugiono, Sadrakh (Publisher: Bethel Press; Unit Penerbit: STT Bethel Indonesia Jakarta, 2024)
Coaching for adults can be developed based on behavioristic, cognitive and constructivist learning concepts. However, coaching for adults that involve students from the beginning of the coaching design until the final evaluation requires an appropriate learning concept, namely participatory learning. This research aims to develop a concept of formation for Christian adults by utilizing participatory learning. The research method used is descriptive qualitative. To produce a participatory coaching concept, an analysis was carried out of the characteristics of coaching for Christian adults and the concept of participatory learning. A participatory coaching concept was developed based on the results of the following analysis stage. The research results are based on participatory coaching for Christian adults, which consists of principles of participatory coaching and steps to develop participatory coaching for Christian adults.